MORAL REASONING AND INTENTION TO PERFORM UNETHICAL BEHAVIOUR OF LECTURERS IN MALAYSIA - Ishak, Nurul Khair; Haron, Hasnah; Zainuddin, Yuserrie (I-iECONS e-proceedings, 2023)
The process of deciding what is right or wrong in a particular scenario is known as moral reasoning. Moral reasoning is important as it will help to shape an individual’s intention whether to perform or not to perform an unethical behaviour. This study will examine the level of moral reasoning of lecturers in public universities of Malaysia and examine its relationship to intention to perform unethical behaviour. The Defining Issues Test 2 (DIT2) via N2 scores was used to measure the level of moral reasoning of lecturers. Intention to perform unethical behaviour was measured using ethical dilemmas scenarios. Online survey was sent to 30 lecturers of the Faculty of Business/ Management from 20 public universities. 130 responses were received, and data collected was sent to the Centre for the Study of Ethical Development University of Alabama for reliability test, scoring and analysis, as it is copyrighted. Only 83 responses passed the DIT2 reliability test and was then used for further analysis. The result shows that the N2 score of lecturers is at the low level of 23.39 which falls in Kohlberg’s Cognitive Moral Development stage 2 and 3 representing the personal interest schema. The study also found that moral reasoning of lecturers does not affect their intention to perform unethical behaviour. This could be because the level of moral reasoning of lecturers are at a low level and thus do not affect intention to perform unethical behaviour. Thus, efforts should be taken to develop the moral reasoning to a higher level such as exposing them to ethics courses and ethics training program that can increase their cognitive moral development to a higher level so that they do not only focus on self but also on law, social order and universal ethical principles.